Factors associated with seropositivity for SARS-CoV-2 in patients treated at a hospital in the Peruvian highlands - Vera-Ponce, Víctor J. (2021)
Background: COVID 19 is an infectious disease caused by SARS-CoV-2 that has affected Peru on a large scale. Potential clinical and/or epidemiological factors that are related to the positivity of SARS-CoV-2 in the high Andean population are not documented. Objective: To determine factors associated with positivity of SARS-CoV-2 in people living in Ancash. Material and methods: Analytical transversal study. We used the records of patients treated for suspected COVID-19 in a public hospital in Huaraz in March-May 2020. Prevalence ratios (PR) with confidence intervals were estimated. In simple regression analysis, prevalence ratios and 95% confidence intervals were estimated, using Poisson distribution family, log-link function and robust variance. Results: Out of 903 patients, 13.7% tested positive for SARS-CoV-2. In simple regression, male (RP=2.98), cough (RP=2.27), respiratory distress (RP=2.97), diarrhea (RP=2.69), general malaise (RP=1.82), odynophagia (RP=1.69) were positively associated with having a positive SARS-CoV-2 test. In the multiple regressions, the association was maintained in four characteristics: being male (RP=2.7), having a cough (RP=1.45), respiratory distress (RP=2.15), and diarrhea (RP=1.89). Conclusion: In high Andean areas, most positive cases present typical symptoms. The factors associated with positivity were male sex and the presence of cough, respiratory difficulty and diarrhea.